Pension programs around the world: determinants of social pension - Alexandra Rudolph; Jan Priebe (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Old age poverty is to become one of the most pressing issues in the coming decades given the demo-graphic trends forecasted. This paper investigates the main instrument to fight old age poverty: Social, non-contributory pension systems. A new comprehensive data set on 172 countries over the 2001-2013 period on the provision of social pension across the world allows us to investigate recent trends in social pension implementation and test internal and external political economy drivers of the process. By using a first order Markov transition model to account for the state dependence inherent in public pension provision, we find that demand factors such as demographic trends drives the decision to reform internally. External actors can support the continuance of social pension especially in developing countries. Thus, international influence seems to be effective in enhancing the instruments to fight old-age poverty.
Keywords: H55; J14; I38; 330